So going through some exercises on understanding Boolean Algebra Q1 P*Q+P*(Q+S) (PQ)+P*(Q+S) Because P and Q are common factors they can be canceled out and the simplified statement is = P*(Q+S) Q2 is P+Q+P*(Q'+S) (P+Q+P)*(Q'+S) But this has got me confused as to how to simplify it further. I know that Q+Q' = 1 but Q*Q' = 0, but also Q*/+Q = Q. But i'm not sure how to start attacking it. Truth Table would be PQS | Equation 000 0 001 0 010 1 011 1 100 1 101 1 110 1 111 1 Q3 (R+S*T)*(R+S'*T) (R*R+R*S'+R*T)*(R*R+R*S+R*T) (R*S'+T)*(R*S+T) (R*0+T) (R+T) All are common factors so, R*R= R, S*S'= 0, T*T=T Simplified = (R+T) It looks wrong to me I think the answer is (R) but I cant tell where I went wrong. Is Q1 Correct and is someone able to help step by step to explain what I need to do to work with Q2 and Q3?